Principles of Innovation Management in Transport - Alexey Yuryevich Smirnov; Vladimir Leonidovich Alexandrov (Управленческое консультирование)
The purpose of scientific research is to ensure the effective management of innovation in transport. The main results of the study were the definition of the principles ensuring the effective functioning of vehicles in the conditions of their reduction and increase in prices for basic commodities.